Mobile ad hoc networks under wormhole attack: A simulation study - Al-Safwani, Nadher M. A.; Hassan, Suhaidi; M. Kadhum, Mohammed (2011)
Security has become the main concern to grant protected communication between mobile nodes in an unfriendly environment.Wireless Ad Hoc network might be unprotected against attacks by malicious nodes.This paper evaluates the impact of some adversary attack on mobile Ad Hoc Network (MANET) system which has been tested using QualNet simulator.Moreover, it investigates the active and passive attack on MANET.At the same time, it measures the performance of MANET with and without these attacks.The simulation is done on data link layer and network layer of mobile nodes in wireless Ad Hoc network.The results of this evaluation are very important to estimate the deployment of the MANET nodes for security. Furthermore, this study analyzes the performance of MANET and performs “what-if” analyses to optimize them.